Sustainable agriculture, food security and hunger free India - Agrawal, K P (Indian Farming, 2015)
Food security is defined as the availability accessability and nutritional adequacy of food to maintain a healthy and active life. Food crisis is a global phenomenon and has led to riots in several countries of the world. The situation is more grave in Sub- Saharan Africa where millions of young children and mothers suffer from hunger malnutrition, anaemia, etc. Food crisis may aggravate with population explosion which may reach to a level of 900 crore by 2050 and African and South Asian countries will be more affected.